Simulations of hydro-mechanical deep drawing using Voronoi model and real microstructure model. (2017) - Wei, Dongbin; Luo, Liang; Sato, Hideki; Jiang, Zhengyi; Manabe, Kenichi
Abstract: Micro hydroforming is promising for fabricating complex micro components with a high aspect ratio. The aim of this study is to deepen the understanding of the size effects in micro hydroforming. Experimental work and FEM simulations of micro hydro-mechanical deep drawing (MHDD) were conducted. Voronoi model and real microstructure model were established. Real grain morphology can be considered in the real microstructure model. Local thinning in critical area of the drawn cups due to size effects can be predicted by the models. The simulation results agree with the MHDD test results.